2018
DOI: 10.1038/s41586-018-0266-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 secreted by myeloid cells drives castration-resistant prostate cancer

Abstract: Patients with prostate cancer frequently show resistance to androgen-deprivation therapy, a condition known as castration-resistant prostate cancer (CRPC). Acquiring a better understanding of the mechanisms that control the development of CRPC remains an unmet clinical need. The well-established dependency of cancer cells on the tumour microenvironment indicates that the microenvironment might control the emergence of CRPC. Here we identify IL-23 produced by myeloid-derived suppressor cells (MDSCs) as a driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
312
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(326 citation statements)
references
References 45 publications
14
312
0
Order By: Relevance
“…Finally, immunofluorescence and flow cytometry analyses revealed that, in patients with castration-resistant prostate cancer (CRPC), tumor-infiltrating myeloid-derived suppressor cells with the neutrophil phenotype (CD11b + CD33 + CD15 + cells, polymorphonuclear cell-myeloid-derived suppressor cells) express IL-23. 56 In summary, we show that highly pure neutrophils express IL-23, which is capable…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Finally, immunofluorescence and flow cytometry analyses revealed that, in patients with castration-resistant prostate cancer (CRPC), tumor-infiltrating myeloid-derived suppressor cells with the neutrophil phenotype (CD11b + CD33 + CD15 + cells, polymorphonuclear cell-myeloid-derived suppressor cells) express IL-23. 56 In summary, we show that highly pure neutrophils express IL-23, which is capable…”
Section: Discussionmentioning
confidence: 68%
“…However, in these experiments the infected neutrophils were also reported to express IL‐17, which, according to our previous work, does not occur. Finally, immunofluorescence and flow cytometry analyses revealed that, in patients with castration‐resistant prostate cancer (CRPC), tumor‐infiltrating myeloid‐derived suppressor cells with the neutrophil phenotype (CD11b + CD33 + CD15 + cells, polymorphonuclear cell‐myeloid‐derived suppressor cells) express IL‐23 …”
Section: Discussionmentioning
confidence: 99%
“…Arginase‐1 expression and activity in monocytes and MDSCs varies considerably between individuals, which may explain why we did not find a consistent effect on arginase‐1 expression in this study. IL23 secreted by granulocytic MDSCs is observed to be involved in CRPC . However, in this study, we focus on monocytic MDSCs and we did not observe a significant increase in IL23 expression in the monocytic MDSCs generated by prostate cancer cell CM.…”
Section: Discussionmentioning
confidence: 65%
“…High numbers of MDSCs in a Pten -/setting provide a protective effect on PCa cells from senescence, therefore sustaining tumour growth 26 , 27 . Mechanistically this has been observed to occur in CRPC patients and in transgenic prostate cancer models through the activation of the AR signalling due to paracrine IL-23 secretion by MDSCs 28 . Furthermore, influx of tumour MDSCs has been detected following RT, an observation which has been previously associated with the RT-induced up-regulation of STING expression in tumour cells 19 , 29 , 30 .…”
Section: Discussionmentioning
confidence: 98%